11+ for kids Manual. A warm-up programme to prevent injuries in children's football - Rössler, R.; Faude, O.; Bizzini, M.; Junge, A.; Dvorák, J. (FIFA Medical and research centre, 2016)
Contents: INTRODUCTION CONTENT AND STRUCTURE CORRECT EXECUTION AND CORE ELEMENTS CHANGING TO THE NEXT LEVEL OF DIFFICULTY ORGANISATION ON THE PITCH THE FIFA 11+ FOR KIDS PROGRAMME EXERCISE 1: "ALERTNESS" RUNNING GAME EXERCISE 2: SKATING JUMPS EXERCISE 3: SINGLE-LEG STANCE EXERCISE 4: PRESS-UPS EXERCISE 5: SINGLE-LEG JUMPS EXERCISE 6: SPIDERMAN EXERCISE 7: SIDEWAYS ROLL ANNEXE: FREQUENTLY ASKED QUESTIONS SUMMARY